Review of surgical spproaches for posterior fossa tumors in pediatric population and illustrative cases - Alick Durão Moreira; Antonio Rosa Bellas; Marcelo Pousa; Tatiana Protzenko (Brazilian Society for Pediatric Neurosurgery, 2023)
Introduction/Background: Posterior fossa tumors are common in the pediatric population, and various surgical approaches have been described to reach them based on their specific location. This paper aims to review the most common posterior fossa approaches in pediatric patients and present illustrative cases to provide insights into their successful application in specific clinical scenarios. Case report:  Three cases are presented, each demonstrating a different approach and surgical outcome. Case 1 involved a telovelar approach for the resection of a medulloblastoma, resulting in complete removal without neurological deficits. Case 2 required a combination of telovelar and supracerebellar infratentorial approaches to achieve gross total resection of a pilocytic astrocytoma. In Case 3, an occipital transtentorial approach was utilized to access and completely resect an atypical teratoid rhabdoid tumor. Connclusion:  The paper discusses the telovelar and transvermian approaches, the supracerebellar infratentorial approach, the transtentorial suboccipital approach, and intraventricular endoscopy as individual or combined approaches for posterior fossa tumors. The presented cases highlight the importance of tailoring the surgical approach to each patient and provide valuable insights for neurosurgeons managing similar clinical scenarios.